Examining Platform Owner Compliance and Autonomous Complementor Behavior in Open Banking Platforms - Mansour, Osama (Thirty-Third European Conference on Information Systems, Amman, Jordan, 2025-06-16 - 2025-06-18, 2025)
The revised Payment Services Directive (PSD2) by the EU is disrupting banks and requiring them to provide third-party providers (TPPs) access to customer data. PSD2 aims to promote innovation and competition by enabling TPPs to leverage data to develop payment services. To comply, banks develop platforms where TPPs can use APIs to access data. This is described as open banking, marking a shift toward platformization in banking. The paper explores the competitive relationship between banks and TPPs as banks pursue compliance while engaging with TPPs offering competing services. It shows that banks perceive TPPs as a competitive threat, particularly when platform exchanges yield no tangible gains, despite significant technology investments. It also demonstrates how banks and TPPs engage through platform integration of services and connections via data aggregators. The paper advances digital platform literature by illustrating emerging relationships and conditions for competition and partnerships within regulated digital platforms.
Keywords: Digital platforms; PSD2; Banking; Digital transformation; Compliance; Innovation; Fintech; Open Banking